Optimizing pediatric anesthesia: A randomized controlled trial comparing oral gabapentin and lorazepam on intubation-induced hemodynamic responses - Munawar, Emil; Riswandi; Jasa, Zafrullah Khany (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: Endotracheal intubation in pediatric patients undergoing elective surgery can trigger hemodynamic response, including increased blood pressure and heart rate, due to sympathetic stimulation. Premedication is required to attenuate these responses. However, the comparative effectiveness of gabapentin and lorazepam remains to be investigated.Objectives: This study aims to evaluate and compare the effects of gabapentin and lorazepam premedication on blood pressure and heart rate during tracheal intubation in pediatric patients.Methods: This randomized controlled clinical trial involved 64 pediatric patients undergoing elective surgery. They were divided into two groups: the gabapentin group (15 mg/kg) and the lorazepam group (0.025 mg/kg). Hemodynamic parameters were measured before and after intubation. Results: The study results showed that the gabapentin group had lower systolic blood pressure, diastolic blood pressure, and mean arterial pressure (MAP) compared to the lorazepam group after intubation (p<0.05). Gabapentin was also more effective in maintaining blood pressure stability than lorazepam, while both groups showed comparable heart rate parameters (p > 0.05).Conclusion: Gabapentin premedication is more effective in suppressing the surge in blood pressure caused by intubation than lorazepam, while lorazepam is more significant in reducing heart rate. Overall, gabapentin may be a more optimal premedication option for maintaining hemodynamic stability in pediatric patients undergoing elective surgery.